Evidence for late Middle Pleistocene glaciation of the British margin of the southern North Sea. (1st February 2016) - White, Tom S.; Bridgland, David R.; Westaway, Rob; Straw, Allan
ABSTRACT: The timing and extent of late Middle Pleistocene glaciations in England and the southern North Sea are controversial topics. The recent Trent Valley Palaeolithic Project uncovered evidence for a post‐Anglian, pre‐Devensian glaciation that affected much of central and eastern England; the Wragby Till of Lincolnshire is associated with this glacial event, attributed here to Marine Oxygen Isotope Stage (MIS) 8. Coeval glacigenic deposits in the Middle Trent suggest that both western and eastern lobes of MIS 8 ice reached the Derby area. These various deposits have been assigned previously to MIS 12, 10 or 6, although the last can be excluded for the Wragby Till, which is overlain by Trent terrace deposits assigned to MIS 7 (from biostratigraphy and amino acid dating). The disposition of these glacigenic deposits within the landscape, particularly in relation to terrace deposits of the ancestral River Trent, and the absence of MIS 11 and 9 deposits within the footprint of the glaciation also provide compelling evidence. At its maximum extent in eastern England the MIS 8 ice reached the Peterborough area; identifying its extension (or otherwise) into areas such as north‐west Norfolk and the West Midlands requires further work.